RELEVANCE OF SOCIAL CAPITAL FOR COMMUNITY EMPOWORMENT AND CONSERVATION EDUCATION IN ECOTOURISM DEVELOPMENT OF RURAL WEST JAVA, INDONESIA - Sunkar, Aryzana; Meilani, Resti; Harini Muntasib, E.K.S (ITB Journal Publisher, LPPM ITB, 2015)
Ecotourism success would depend on the community readiness to welcome and participate in tourism in terms of their attitudes towards tourism development, commitment, and capacity. These are related with expanding access to natural resources which are determined by the availability of local networks, collective actions, mutual trust, and social norms, which constitute social capital. Therefore, ecotourism as a tool of rural economic diversification requires social capital for its development. This study attempts to identify the relevance of social capital in empowering rural communities of West Java and enhancing conservation education for ecotourism development. The research was conducted in the Districts of Bogor, Sukabumi and Cianjur of West Java, Indonesia. The study employed a mixed method with predominantly qualitative approach to obtain data. Findings indicated that communities with higher social capital have higher potentials to induce ecotourism development through empowering community and minimize risks of environmental degradation through conservation education.